2017
DOI: 10.1039/c7ra09444b
|View full text |Cite
|
Sign up to set email alerts
|

Non-toxic luminescent Au Nanoclusters@Montmorillonite nanocomposites powders for latent fingerprint development

Abstract: Non-toxic Au nanoclusters@montmorillonite (AuNCs@MMT) nanocomposites with strong red fluorescence are prepared by a microwave (MW)-assisted synthesis method and immobilize Au NCs into sodium MMT clay matrix via electrostatic interaction. Due to the immobilization of Au NCs in the layered structure of the MMT clay matrix, the formative AuNCs@MMT nanocomposites show high emission, stable chemical features and less toxicity. The obtained Au NCs and AuNCs@MMT nanopowders were characterized by using UV-visible abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…All the articles below refer to the application of micron-sized particles. Preliminary/Pilot studies : Several kinds of compounds were proposed to detect fingermarks on non-porous substrates through powder dusting: ABC dry fire extinguisher powder [ 354 ], Fuller’s earth [ 355 ], anthracene and naphthalene [ 356 ], BaTiO 3 :Dy 3+ microspheres [ 357 ], chitosan-tripolyphosphate microparticles [ 358 ], La 2 (MoO 4 ) 3 :Eu 3+ microcrystals [ 359 ], phenyl-doped graphitic carbon nitride [ 360 ], bis(salicylidene)cyclohexyl-1,2-diamino zinc(II) complex [ 361 ], functionalized montmorillonite [ 362 , 363 ], carbon dot@TiO 2 core-shell composite [ 288 ], household powders such as gram flour, coriander, cumin or black pepper [ 364 ], Ca 4 (PO 4 ) 2 O:Eu 2+ phosphors [ 365 ], Eu(Phen) 2 complex intercalated clay hybrids [ 366 ], AIE-based magnetic powder doped with tetraphenylethene derivatives [ 367 ], pyrene [ 368 ], silica microparticles coated with phenanthro imidazole derivative [ 369 ], europium (III) coordination polymer [ 370 ], Yb 3+ /Er 3+ co-doped ceramics presenting upconversion properties [ 371 ], cationic dye – diatomite composite [ 372 ], benzazole-doped silica microparticles [ 373 ], Yb 3+ /Er 3+ /Tm 3+ doped fluorides presenting upconversion properties [ 374 ], porous graphitic carbon nitride [ 375 ], YBO 3 :Eu 3+ /Tb 3+ phosphors [ 376 ], Mg 2 TiO 4 :Mn 4+ phosphor [ 377 ], carbazolyl-based phosphor [ 378 ], and AIE-based imidazole derivatives [ 379 ]. It should be emphasized that several of these studies are conducted with an extremely low number of donors leaving fresh, sebum-rich fingermarks.…”
Section: Fingermark Composition and Detectionmentioning
confidence: 99%
“…All the articles below refer to the application of micron-sized particles. Preliminary/Pilot studies : Several kinds of compounds were proposed to detect fingermarks on non-porous substrates through powder dusting: ABC dry fire extinguisher powder [ 354 ], Fuller’s earth [ 355 ], anthracene and naphthalene [ 356 ], BaTiO 3 :Dy 3+ microspheres [ 357 ], chitosan-tripolyphosphate microparticles [ 358 ], La 2 (MoO 4 ) 3 :Eu 3+ microcrystals [ 359 ], phenyl-doped graphitic carbon nitride [ 360 ], bis(salicylidene)cyclohexyl-1,2-diamino zinc(II) complex [ 361 ], functionalized montmorillonite [ 362 , 363 ], carbon dot@TiO 2 core-shell composite [ 288 ], household powders such as gram flour, coriander, cumin or black pepper [ 364 ], Ca 4 (PO 4 ) 2 O:Eu 2+ phosphors [ 365 ], Eu(Phen) 2 complex intercalated clay hybrids [ 366 ], AIE-based magnetic powder doped with tetraphenylethene derivatives [ 367 ], pyrene [ 368 ], silica microparticles coated with phenanthro imidazole derivative [ 369 ], europium (III) coordination polymer [ 370 ], Yb 3+ /Er 3+ co-doped ceramics presenting upconversion properties [ 371 ], cationic dye – diatomite composite [ 372 ], benzazole-doped silica microparticles [ 373 ], Yb 3+ /Er 3+ /Tm 3+ doped fluorides presenting upconversion properties [ 374 ], porous graphitic carbon nitride [ 375 ], YBO 3 :Eu 3+ /Tb 3+ phosphors [ 376 ], Mg 2 TiO 4 :Mn 4+ phosphor [ 377 ], carbazolyl-based phosphor [ 378 ], and AIE-based imidazole derivatives [ 379 ]. It should be emphasized that several of these studies are conducted with an extremely low number of donors leaving fresh, sebum-rich fingermarks.…”
Section: Fingermark Composition and Detectionmentioning
confidence: 99%
“…Nanomaterials such as magnetic nanoparticles, semiconductor quantum dots and their composites, metals and their oxide nanoclusters, and carbon dots have been greatly attractive in latent fingerprint detection because of their good magnetic properties, sole dependency on size photoluminescence with stable emission, high quantum yield and good biocompatibility [ 113 ].…”
Section: Reuse Applications For the Spent Adsorbentsmentioning
confidence: 99%
“…Since 19th century, fingerprints have been used as one of the most important means for criminal investigations and many studies have focused on the development of fingerprint detection techniques. [1] Among the emerging strategies, the use of luminescent nanoparticles, especially rare earth fluorescent nanomaterials, [2][3][4] gold nanoparticles [5,6] and quantum dots, [7,8] was regarded as the most notable one in the field. [9] It was found that small powder particles adhere better on fingermark residue and then the detected residue are easily observed in virtue of the fluorescent properties of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%